Integrating policy targets into product environmental impact assessments: A case study with Finnish agricultural products - Kyttä, Venla; Ghani, Hafiz Usman; Lindfors, Kim; Heikkinen, Jaakko; Palosuo, Taru (Elsevier, 2025)
Political objectives aimed at reducing environmental impacts currently face challenges in effectively assessing achievement at product level. Applying the principles of Absolute Environmental Sustainability Assessment (AESA, or Planetary Boundaries-based Life Cycle Assessment, PB-LCA) to these targets could be a way forward to evaluate a product's performance against political targets. Here, we explore the possibilities of assigning emission budgets for agricultural products based on political and scientific targets utilising the principles of PB-LCA. We tested these principles by assessing a few Finnish agricultural products; wheat, peas, milk, and beef. First, we identified national and EU-level political targets relevant to agricultural products produced in Finland. Then these targets alongside scientific planetary boundary targets were translated to emission budgets for products by first sharing the targets equal per capita and then using two different sharing principles; calorie-based and nutrition-based. In the last step, the environmental impacts of the products were compared with the emission budget assigned to each product. The results demonstrated that the method used to assign the emission budgets affects the results, nutrition-based sharing leading to better performance compared to calorie-based sharing. Beef exceeded its budget in almost all impact categories, while the results for milk and peas depended on the sharing principle used. Wheat's impacts were within the budget across all categories. The results show that both political and scientific targets can evaluate a product's sustainability performance, and comparing environmental impacts against political targets can provide new insights for decision-makers.
Keywords: sustainable production; PB-LCA; emission budget; environmental targets; sustainable food